EXPERIMENTAL ALTERATION OF MOLYBDENITE: EVALUATION OF THE RE-OS SYSTEM, INFRARED SPECTROSCOPIC PROFILE AND POLYTYPE - THE PGE CONTENT OF FLUIDS AT MAGMATIC TEMPERATURES - Suzuki K.; Kagi H.; Nara M.; Takano B.; Nozaki Y. (My University, 2000)
Experiments have been carried out to clarify the effect of alteration on Re-Os system, near infrared (NIR)-infrared (IR) spectroscopic characteristics and polytype of a natural molybdenite mineral (MoS2). The molybdenite sample was placed in H2O and various media of 0.1 mol/L NaCl, NaHCO3, CaCl2, and AlCl3 solutions, and heated in a sealed quartz tube at a temperature of 180°C for 20 d. The unaltered and altered samples were subsequently used for analysis of Re and Os, NIR microscopic observation, and NIR-IR spectroscopy, and microfocus X-ray diffraction (XRD). Molybdenites subjected to NaCl and NaHCO3 solutions give younger Re-Os ages than that of the original unaltered molybdenite. No significant changes in d spacing and width of micro-XRD patterns can be found in these altered molybdenite, indicating the possibility of Re-Os fractionation without significant structural conversion of molybdenite mineral. These results strongly suggest that the Re-Os system in molybdenite would be frequently disturbed if it has experienced alteration, because alteration by the low salinity (<1%), low temperature (~180°C) hydrothermal solution containing NaCl and/or CO2 is commonly found in the natural environment. We maintain, therefore, that one set of analyses of Re and Os in a sample is not enough to determine whether the obtained Re-Os age has been affected by postdepositional alteration, but systematic replicate analyses are indispensable. Additionally, pulverizing all the collected molybdenite in a sample might give misleading results because portions, which have been altered and experienced Re-Os fractionation, may possibly mix into the undisturbed sample and be homogenized. The molybdenite used for the experiment was originally opaque under NIR light. Infrared microscopic and spectroscopic profiles show that some parts of the molybdenite subjected to CaCl2 and AlCl3 solutions become transparent to NIR. Increased NIR transmittance is possibly attributed to the removal of the impurity band in molybdenite. It was also found in this study, however, that change in IR profile does not correlate with the Re-Os fractionation and, therefore, IR measurement solely is not useful to detect disturbance of Re-Os systematics of molybdenite in alteration.